Marble Museum of Vila Viçosa, Portugal - A Mirror of Geological and Mining Heritage - Martins, Ruben (2020)
Raquel de Castro Marble’s Museum was built in an old quarry of ornamental marble located in one of the entrances of Vila Viçosa, Alto Alentejo – Portugal. It’s a space intended to preserve all the knowledge acquired over decades of exploitation and processing of the Worldwide know stone Estremoz Marble, regionally called "White Gold”. The name of the museum, Raquel de Castro is due to the former owner of the quarry that donated in life the space to the Town Hall of Vila Viçosa. The importance of this industry to the region's economy has profoundly affected the lives of its people and is always strongly linked to the natural stone sector. The contents arranged logically and sequentially, guide the visitor in the most varied aspects, from the geological, historical, technological, environmental and social framework. All the themes are approached in a scientific and practical way, making the museum an area of knowledge and culture constituting a portrait where the populations and industrialists of the region can be reviewed.